Uji Aktivitas Antijamur Gel Serbuk Lidah Buaya (Aloe vera L.) Berbasis Carbopol 934 Terhadap Candida albicans dan Trichophyton mentagrophytes - Hani Afifah; Setyo Nurwaini (Universitas Muhammadiyah Surakarta, 2018)
Fungal infections that occur in the skin and nails were caused by fungi such as Candida albicans and Trichophyton mentagrophytes. Aloe vera contains saponins and acemannan that were effective as an antifungal. This study aims to determine the effect of carbopol concentration variation on aloe vera gel to antifungal activity of Candida albicans and Trichophyton mentagrophytes.Aloe vera powder was obtained from freeze drying aloe vera juice which had been frozen. Aloe vera powder was formulated in gel form using carbopol base with concentration 0.5; 1.0; 1.5; and 2.0 %w/w. The aloe vera gel was tested for its physical properties and then tested the antifungal activity using the diffusion method of wells.The result of evaluation of physical properties showed the high concentration of carbopol then pH, viscosity, adhesiveness increased, and spreading capacity decreased. The results of antifungal activity test showed that aloe vera powder had activity on Candida albicans and Trichophyton mentagrophytes with inhibition zone of 15 ± 3 mm and 13 ± 0,5 mm. Aloe vera gel test results with variation of carbopol concentration 0.5; 1.0; 1.5; and 2.0 %w/w did not affect the antifungal activity of Candida albicans and Trichophyton mentagrophytes.